Menumbuhkan Jiwa Wirausaha Siswa SMK Siang Surabaya - Endang Pudji Purwanti; Imam Sutrisno; Didik Dwi Suharso (CV. Creative Tugu Pena, 2025)
Vocational education plays a strategic role in preparing a skilled workforce for both industry and entrepreneurship. However, many vocational school graduates face challenges in launching their own businesses due to insufficient entrepreneurial competencies. This study explores effective strategies for cultivating an entrepreneurial mindset among students at SMK Siang Surabaya. A qualitative research approach was employed, incorporating interviews, observations, and literature review. The findings reveal that integrating entrepreneurship education into the curriculum, offering business skills training, and implementing internship programs significantly enhance students' interest in and preparedness for entrepreneurship. The study underscores the value of a comprehensive support system, including mentorship, access to seed funding, and partnerships with local business practitioners, in addressing common obstacles such as low self-confidence, limited marketing knowledge, and financial constraints. These results provide actionable insights for vocational schools, educators, and policymakers in developing entrepreneurship-oriented educational strategies. By identifying key success factors, this research contributes to the advancement of vocational education and the promotion of sustainable youth entrepreneurship.